The Impact of the Free Nutritious Meals Program (MBG) on Regional Development: An Analysis of Food Security, Local Economic Growth, and Sustainable Development in Indonesia - Siti Nurjanah; Jopie Tommy Rompas; Maulana Irfan Andriansyah (Journal Research of Social Science, Economics, and Management, 2026)
The Free Nutritious Meals Program (MBG) is one of Indonesia’s strategic policies aimed at improving nutritional status and strengthening human capital development. Beyond its primary objective of improving nutrition, the program has significant potential to stimulate regional development through enhanced food security and local economic growth. This study analyzes the relationship between the MBG program, regional food security, local economic growth, and human development. Using a qualitative descriptive approach through a literature review, this study examined academic publications, international reports, and policy documents related to school feeding programs, food security, and regional development. The findings indicate that MBG generates multidimensional impacts. First, MBG strengthens regional food security by creating stable demand for local agricultural products. Second, it generates economic multiplier effects through increased income for farmers, micro and small enterprises, and supporting sectors. Third, it contributes to human development by improving nutritional status, health outcomes, and educational performance. This study developed the MBG Local Development Cycle Model to explain the relationship between MBG, food security, local economic growth, and sustainable regional development. The findings demonstrate that MBG should be viewed not only as a social assistance program but also as a strategic instrument for regional development and the achievement of the Sustainable Development Goals (SDGs).